2005
DOI: 10.1007/s10800-005-9003-0
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical incineration of oxalic acid: Reactivity and engineering parameters

Abstract: Mass transfer measurements were carried out to test a disk-shaped parallel-plate electrochemical cell, based on a new design. The impinging-jet-cell concept, confined between parallel plates, was adapted to a configuration with one central inlet and several peripheral exit sections, leading to more effective hydrodynamics within the cell. Measurements of mass transfer coefficient were performed using the limiting diffusion current technique based on ferro-cyanide ion oxidation, and overall mass transfer coeffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 35 publications
(40 reference statements)
5
47
0
Order By: Relevance
“…According to literature data, the temperature effect on OA degradation strongly depends on the anodic material nature. With BDD, a temperature increase gave rise to a slight change in OA abatement [22,29], while a drastic increase at IrO2 based anodes was observed [22,28]. In the present system, a Table 4.…”
Section: Effect Of Temperature On Oa Removal and Reaction Kineticsmentioning
confidence: 73%
See 3 more Smart Citations
“…According to literature data, the temperature effect on OA degradation strongly depends on the anodic material nature. With BDD, a temperature increase gave rise to a slight change in OA abatement [22,29], while a drastic increase at IrO2 based anodes was observed [22,28]. In the present system, a Table 4.…”
Section: Effect Of Temperature On Oa Removal and Reaction Kineticsmentioning
confidence: 73%
“…Furthermore, temperature effect (T) was investigated in the range from 25 to 60 °C. During the electrolysis, OA residual content was determined using a conventional titration method with KMnO4 [22].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, some studies reported that the current efficiencies obtained with Si/BDD in oxidising 4-chlorophenol (Gherardini et al, 2001), 2-naphthol (Panizza andCerisola, 2004), chloranilic acid (Martinez-Huitle et al, 2004a), and chlorpyrifos pesticide (Samet et al, 2010b) were higher than those obtained with PbO 2 anodes. In contrast, Martinez-Huitle et al (2004b) showed that the oxidation of oxalic acid was faster at Ti/PbO 2 than at BDD, because the interaction of the oxalic acid with the PbO 2 surface was particularly strong, and its anodic oxidation was limited only by mass transfer at higher current densities and lower substrate concentrations. Recently, Flox et al (2009) have demonstrated that m-cresol is more rapidly removed with PbO 2 than with BDD.…”
Section: Dimethoate (Oo-dimethyl S-[2-(methylamino)-2-oxoethyl] Phosmentioning
confidence: 90%